-3(5x+3)-(x-3)=

Simple and best practice solution for -3(5x+3)-(x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5x+3)-(x-3)= equation:


Simplifying
-3(5x + 3) + -1(x + -3) = 0

Reorder the terms:
-3(3 + 5x) + -1(x + -3) = 0
(3 * -3 + 5x * -3) + -1(x + -3) = 0
(-9 + -15x) + -1(x + -3) = 0

Reorder the terms:
-9 + -15x + -1(-3 + x) = 0
-9 + -15x + (-3 * -1 + x * -1) = 0
-9 + -15x + (3 + -1x) = 0

Reorder the terms:
-9 + 3 + -15x + -1x = 0

Combine like terms: -9 + 3 = -6
-6 + -15x + -1x = 0

Combine like terms: -15x + -1x = -16x
-6 + -16x = 0

Solving
-6 + -16x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -16x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -16x = 0 + 6
-16x = 0 + 6

Combine like terms: 0 + 6 = 6
-16x = 6

Divide each side by '-16'.
x = -0.375

Simplifying
x = -0.375

See similar equations:

| 2.5x+5=20-3x | | 15c+7w=47 | | 18x^2+48x-96= | | Y=-14+6x | | 5n-3=29+n | | X-5.2=1.92 | | 3y+4r=5y+7r | | x-7/3=-21 | | E/9=6 | | 5(5x+5)+5(5x-2)= | | 8x+2=6x-28 | | 240=4xX+40 | | -2y+4=5y+6y | | -394/4=-401/4-c | | .5p-3.45=-1.2 | | 3(2x-5)+31=15 | | 5x-9+11x-8= | | y=20x+-20 | | 3.9x=2.4x+13.5 | | 3x^3=5x | | -(3x-3)-5(5x+3)= | | -11.1s=-16s-8.33 | | 4x-2=n-8 | | -x-5=x+11 | | 28+(x-36)=180 | | 8y+3=4y+5y | | y=-3(x-7)*2+5 | | -3(3x-5)-3(4x+4)= | | 90+2x-16=180 | | 3(5x-2)-3(x+4)= | | 12-(-7)-8= | | -0.2x-0.6=1.2x-0.83 |

Equations solver categories